Preparation of Mn/Mg/Ce Ternary Ozone Catalyst and Its Mechanism for the Degradation of Printing and Dyeing Wastewater - Zhang, Shuai; Ren, Huixue; Fu, Kaifang; Cheng, Wenqing; Wu, Daoji; Luo, Congwei; Jiang, Shengyun; Li, Jie; Zhang, Mingyue (Frontiers in Energy Research, 2022)
The printing and dyeing wastewater produced by different dyes and printing and dyeing processes have different components. These wastewater have high toxicity, high organic concentration, and deep chromaticity. Ozone catalytic oxidation is a very promising technical method for wastewater treatment. In this paper, Mn/Mg/Ce ternary catalyst was prepared, and the ozone catalytic oxidation treatment of actual and simulated printing and dyeing wastewater was performed to study the performance of four different carrier catalysts, namely, molecular sieve, silica gel, attapulgite, and nano alumina, by simulated dynamic test. The effects of reaction time, pH, and catalyst dosage on methyl orange degradation were studied. The results showed that under the optimum treatment conditions (120 min, pH 11, and 12.5 g/L catalyst dosage), the degradation rate of methyl orange reached 96% and the removal rate of the chemical oxygen demand of printing and dyeing wastewater reached 48.7%. This study shows that the treatment effect of ozone catalytic oxidation on printing and dyeing wastewater is remarkably improved after catalyst addition. This study provides a new choice of ozone catalyst for the degradation of printing and dyeing wastewaters in the future.